Assembly of Trifluoromethylated Morpholines through Cascade Reactions of Bromoenones with Secondary Amino Alcohols. Issue 30 (2nd August 2018) - Rulev, Alexander Yu.; Romanov, Alexey R.; Kondrashov, Evgeniy V.; Ushakov, Igor A.; Muzalevskiy, Vasiliy M.; Nenajdenko, Valentine G.
Abstract : Fluorinated α‐bromoenones react readily with amino alcohols containing a secondary amino group to give monocyclic morpholine derivatives or unexpected bicyclic compounds containing a morpholine moiety fused with an oxetane ring. The reactions are highly stereoselective. The assembly of these heterocycles starts with an aza‐Michael addition followed by intermolecular substitution and addition processes. Abstract : An efficient method for the synthesis of trifluoromethylated morpholinols and previously unknown bicyclic compounds containing fused morpholine and oxetane rings is reported. The method involves the domino reaction of fluorinated α‐bromoenones with secondary amino alcohols. The one‐pot assembly of both heterocyclic systems is initiated by an aza‐Michael reaction followed by intra‐ or intermolecular bromide substitution and cyclization.